Progress and challenges of 3D-printing technologies in the manufacturing of piezoceramics. Issue 8 (15th April 2021) - Smirnov, Andrey; Chugunov, Svyatoslav; Kholodkova, Anastasia; Isachenkov, Maxim; Vasin, Alexander; Shishkovsky, Igor
Abstract: Piezoceramic materials provide the foundation for essential components of modern engineering applications in the fields of acoustics, sensorics, biomedical devices, and microelectronics. With device miniaturization, the industrial requirements for piezoceramics with complex geometries and improved efficiencies has grown tremendously. Traditionally manufactured piezoceramics demonstrate great piezoelectric properties but poor shape conformity. Additive manufacturing (AM) technologies, being a successful contender in the field of technical ceramics, makes its way into piezoceramics production. AM technology applied to traditional piezoelectric materials has many obstacles to overcome, since typical piezoceramic products require complex and intricate shapes, and often consist of composite materials. As a solution to these problems, AM technology can be transformed into a robust fabrication tool. This review intends to outline the current state of the art of AM technologies applied to the manufacture of piezoceramic materials. Modern piezoceramic materials are described in detail, including the effects of doping and texturing. The properties of piezoceramics and their composites are compared for traditionally and additively manufactured devices. The piezolectric properties of the materials produced using different manufacturing methods are summarized in comprehensive tables and figures, where the emerging trends in physical characteristics are revealed. The pros and cons of AM technologies are discussed, and the problems to be addressed in future work are highlighted.